Studi Kebutuhan Pembelajaran Diferensiasi untuk Meningkatkan Kompetensi Problem solving dalam Pembelajaran IPA - Widayanti, Ria; Suryandari, Kartika Chrysti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
In 21st-century learning, students must have higher-order thinking skills, namely problem-solving competencies. Therefore, a learning approach that can accommodate differences in student characteristics is needed to make the learning process more effective. This study focuses on analyzing the needs of differentiated learning to improve problem-solving competencies in science learning. The research approach uses a qualitative approach. The research method is descriptive qualitative. Data collection methods are interviews and documentation. Participants are second-grade teachers and second-grade students from one of the elementary schools in the Kutowinangun district, totaling 5 out of 16. The selection of participants uses purposive sampling. The research data analysis technique starts from data reduction, data presentation to conclusions. Based on the results of the study, it shows the need for differentiated learning to improve problem-solving competencies in science learning. This is indicated by the diverse levels of readiness, interests, and learning styles of students who require a teaching approach adapted to this diversity. The conclusion of the study is a study of the need for differentiated learning to improve problem-solving in science learning.Pembelajaran abad ke-21, murid harus mempunyai pemikiran tingkat tinggi yaitu kompetensi problem solving. Oleh karena itu, membutuhkan pendekatan pembelajaran yang mampu mengakomodasi perbedaan karakteristik murid agar proses pembelajaran lebih efektif. Penelitian berfokus pada analisis kebutuhan pembelajaran berdiferensiasi untuk meningkatkan kompetensi problem solving dalam pembelajaran IPA. Pendekatan penelitian menggunakan pendekatan kualitatif. Metode penelitian adalah kualitatif deskriptif. Metode pengambilan data yaitu wawancara dan dokumentasi. Partisipan adalah guru kelas II dan murid kelas II dari salah satu SDN di kecamatan Kutowinangun berjumlah 5 dari 16. Pemilihan partisipan menggunakan purposive sampling. Teknik menganalisis data penelitian yaitu dimulai dari reduksi data, penyajian data hingga kesimpulan. Berdasarkan hasil penelitian menunjukkan adanya kebutuhan pembelajaran berdiferensiasi untuk meningkatkan kompetensi problem solving dalam pembelajaran IPA. Hal ini ditunjukkan dari beragamnya tingkat kesiapan, minat, dan gaya belajar murid yang memerlukan pendekatan pengajaran yang disesuaikan dengan keberagaman. Kesimpulan penelitian adalah studi kebutuhan pembelajaran diferensiasi untuk meningkatkan problem solving dalam pembelajaran IPA.